2016
DOI: 10.1016/j.plantsci.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association mapping of stripe rust resistance in Afghan wheat landraces

Abstract: Mining of new genetic resources is of paramount importance to combat the alarming spread of stripe rust disease and breakdown of major resistance genes in wheat. We conducted a genome wide association study on 352 un-utilized Afghan wheat landraces against stripe rust resistance in eight locations. High level of disease variation was observed among locations and a core-set of germplasm showed consistence performance. Linkage disequilibrium (LD) decayed rapidly (R≈0.16 at 0cM) due to germplasm peerless diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
(59 reference statements)
1
38
0
Order By: Relevance
“…All positions are approximations, and thus should be treated as guidelines for future studies. The detailed information of relationships between the QTL identified in this study and previously mapped Yr genes and QTL are based on this result integrated by the BioMercator V4.2 and described in the unpublished data of our research group (Table 3 and Additional file 6) the extent of genetic diversity and the genetic basis of responses to stripe rust in wheat may improve the effectiveness of exploration of genetic resources and enrich breeding for durable stripe rust resistance in wheat [60]. In the current study, 93 Northern Chinese wheat landraces were surveyed under four environments and challenged with a mixture of Pst isolates.…”
Section: Discussionmentioning
confidence: 93%
“…All positions are approximations, and thus should be treated as guidelines for future studies. The detailed information of relationships between the QTL identified in this study and previously mapped Yr genes and QTL are based on this result integrated by the BioMercator V4.2 and described in the unpublished data of our research group (Table 3 and Additional file 6) the extent of genetic diversity and the genetic basis of responses to stripe rust in wheat may improve the effectiveness of exploration of genetic resources and enrich breeding for durable stripe rust resistance in wheat [60]. In the current study, 93 Northern Chinese wheat landraces were surveyed under four environments and challenged with a mixture of Pst isolates.…”
Section: Discussionmentioning
confidence: 93%
“…Another simulation was conducted in order to compare the output from PolySim to a real wheat data set, which is a well‐described allohexaploid species (2 n = 6 x = 42), based on LD and He measurements of SNP markers (Manickavelu, Jighly, & Ban, ; Manickavelu et al., ). The simulation was performed for 1,000 individuals, for each of the allohexaploid genomes and its known progenitors.…”
Section: Methodsmentioning
confidence: 99%
“…Selfing rate was set to 90% (outcrossing 10%) as multiple studies reported variable outcrossing rates for wheat up to 10.6% (Hanson, Mallory‐Smith, Shafii, Thill, & Zemetra, ; Lawrie, Matus‐Cádiz, & Hucl, ). We assumed that our wheat population has a high outcrossing rate because of the massive diversity reported in this germplasm (Manickavelu et al., , ). The simulation was run for 30,000 generations, during which the three diploids emerged after 6,000; 6,200 and 10,000 generations; the allotetraploid evolved after 12,000 generations; and the allohexaploid genome appeared at generation 18,000.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of changes in the predominant races and emergence of new races, many wheat cultivars have become susceptible to stripe rust, thus accelerating the cultivar turnover frequency [7]. Mining of novel genetic resources and the breeding of diseaseresistant cultivars is an effective, economic and environmentally friendly strategy to control stripe rust in wheat [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…They have a greater diversity of genes that respond to abiotic and biotic stresses, such as growth habit; cold; heat or drought tolerance; early growth vigor; competition with weeds and disease tolerance [27]. They could be used as important resources for stripe-rust resistance breeding [12,20,[28][29][30][31]. However, relatively few studies have investigated genetic diversity and stripe rust resistance in wheat landraces from the southern autumnsown spring wheat zone of China.…”
Section: Introductionmentioning
confidence: 99%